Magnesium Alloys - Aliofkhazraei, Mahmood (IntechOpen, 2017)
Magnesium alloys usually have desirable properties including high chemical stability, easy processing and manufacturing, and also lightweight. Magnesium alloys weigh about 70% of aluminum alloy weight and 30% of iron and steel weight. Most of these alloys are used for fabrication of structures in aerospace industries. Magnesium belongs to the second main group of the periodic table of elements (alkaline earth metal) and therefore can't be found in pure state in nature and only exists as a chemical composition. This book collects new developments about magnesium alloys and their use in different industries.